IMPLEMENTASI METODE UCD (User Centered Design) PADA RANCANG BANGUN SISTEM INFORMASI PERPUSTAKAAN SMA N 19 PALEMBANG - Oktrimelda Raburga; Tata Sutabri (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
The library plays a crucial role in enhancing educational institutions as students can improve their knowledge there. However, at the library of SMA Negeri 19 Palembang, some processes such as membership registration, inputting candidate member data, book borrowing and returning, book data input, and book cataloging are still recorded in large books. Therefore, a library information system design is needed to assist and facilitate book circulation to prevent delays in library services. The library information system of SMA Negeri 19 Palembang uses a User-Centered Design approach and UML (Unified Modeling Language) as well as the PHP programming language with a MySQL database. It is expected that with the implementation of this library information system, it can help solve the existing problems in the library and improve knowledge development for students.